T计划 ：跨性别者的异托邦空间 = The T project : a transgender heterotopic space - 符弼钧 Foo, Pi Gin (2019)
As Singapore sees an increase in discussion on LGBT related topics, the transgender community continues to remain an invisible group that is often neglected and misunderstood. Familial and societal discrimination are closely linked to the jeopardy of education, housing and financial difficulties. As such, Singapore’s transgender individuals are at higher risk of homelessness. The T Project is a transgender-led organisation that aims to provide shelter and aid towards homeless transgender Singaporeans. This thesis attempts to utilise the Foucauldian concept of heterotopia to analyse the inner workings and development of the organisation. The T Project displays organisational and operational abilities through transgender-centred activities, breaking the negative transgender stereotypes of which persists among Singaporeans. Its heterotopic nature also gives rise to outward expansion and cross-organisational interactions, enabling The T Project to realise its ethos.